Piquin chili, a wild spice: natural variation in nutraceutical contents - Pérez-Ramírez, Rogelio; Moreno-Ramírez, Yolanda del Rocio; Ruiz-De-La-Cruz, Gilberto; Juárez-Aragón, María Cruz; Aguirre-Mancilla, César Leobardo; Niño-García, Nohemí; Torres-Castillo, Jorge Ariel (Frontiers in Nutrition, 2024)
The piquin chili is a wild spice widely consumed from the South United States to Central America and stands out as a source of flavonoids, essential metabolites with antioxidant properties. The concentrations of flavonoids, carotenoids, and capsaicinoids vary according to regions, maturity stages, and ripening processes. These compounds, which are known for their health benefits and industrial applications, highlight the importance of identifying ideal environmental conditions for collecting fruits with the highest contents. Comprehensive studies of the piquin chili are essential for understanding its properties for the benefit of consumers. This approach fortifies trade, contributes to resource conservation, and advances cultivated chili production.